2008
DOI: 10.1021/ja8037849
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Ruthenium-Alkylidene Catalysts for Ring-Expansion Metathesis Polymerization

Abstract: A series of cyclic Ru-alkylidene catalysts have been prepared and evaluated for their efficiency in ring-expansion metathesis polymerization (REMP). The catalyst structures feature chelating tethers extending from one N-atom of an imidazolylidine ligand to the Ru metal center. The catalyst design is modular in nature, which provided access to Ru-complexes having varying tether lengths, as well as electronically different NHC ligands. Structural impacts of the tether length were unveiled through 1H NMR spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 51 publications
2
125
0
Order By: Relevance
“…The number of n carbons within the ring structure significantly influences the rate of polymerization, the amount of intramolecular cross-metathesis (or chain transfer), and reaction between free catalyst and cyclic polymer. 86 In general, the larger the n, the faster the rate of polymerization and the less likely that the Ru-catalyst will be released from the cyclic polymer. The general mechanism (given in Scheme 6) shows that monomer inserts into the cyclic Ru complex (or initiator) to form a macrocycle.…”
Section: Ring-expansion Polymerizationsmentioning
confidence: 99%
“…The number of n carbons within the ring structure significantly influences the rate of polymerization, the amount of intramolecular cross-metathesis (or chain transfer), and reaction between free catalyst and cyclic polymer. 86 In general, the larger the n, the faster the rate of polymerization and the less likely that the Ru-catalyst will be released from the cyclic polymer. The general mechanism (given in Scheme 6) shows that monomer inserts into the cyclic Ru complex (or initiator) to form a macrocycle.…”
Section: Ring-expansion Polymerizationsmentioning
confidence: 99%
“…Test calculations were carried out to establish the most appropriate theoretical model. Four different functionals B3LYP, MPW1K, M05 and PBE0 were tested to compare the optimized and experimental structures of recently synthesized rutheniumalkylidene complex [8] using double and triple f basis sets (LACVP* and LACV3P*, respectively) as defined in JAGUAR 7.0 suite of programs. Test calculations demonstrated that MPW1K and PBE0 reproduced best the experimental geometry (the largest deviation from experiment was found to be of 0.04 Å for Ru-Cl and Ru-P Scheme 1.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] We have reported a zwitterionic 14 ring-opening polymerization strategy 15 for the synthesis of cyclic polymers from lactones, [16][17][18][19][20][21][22][23] cyclic phosphates, 24 and carbosiloxanes; 25 Zhang has shown this strategy is also effective for generating cyclic poly( peptoid)s. 26 N-heterocyclic carbenes (NHC) have proven useful as intiators for ZROP due to the ability to tune the reactivity of the carbene to that of the monomer. NHC-mediated ZROP has recently been reported in the synthesis of ultra-high molecular weight cyclic polymers up to >900 kDa.…”
Section: Introductionmentioning
confidence: 99%